Terminação intensiva de bovinos com níveis de concentrados à bases de farelo de soja ou DDGS em pastagem de capim-mombaça, sob lotação contínua, no período chuvoso do bioma Amazônia - Roecker, Adriano Nicoli (2022)
Our objective was to evaluate levels of concentrates with soybean meal or DDGS in diets of Nelore cattle in intensive pasture finishing in the rainy period of the Amazon biome. Two experiments were conducted, and the treatments consisted of two levels of concentrates (NC) isonitrogenated at 15 g.kg-1 body weight (BW) and ad libitum, consisting of soybean meal or DDGS as a true protein source (FP). We initially evaluated forage component, performance, carcass characteristic and blood parameters. This was structured according to an entirely randomized design in a 2x2 factorial scheme with two levels of concentrate and two protein sources. We used 154 male Nelore cattle, uncastrated, with initial age of 20±2 months and initial CP of 446±33.3 kg, allocated in 12 plots with 2.5 ha of Megathyrsus maximus (Sin. Panicum maximum) cv. Mombasa and 12 animals per plot. In the second experiment, we evaluated the gas production kinetics and the in vitro methane digestibility of the diets. The experiment was structured according to a randomized block design in a 2x2 factorial scheme, with two levels of concentrate and two protein sources. The diets were constituted according to the consumption or results observed in the first trial. Thus, the NC were in the proportions of: 15 and 17 g kg-1 of CP. We observed that in the NC ad libitum treatment, the forage supply was higher compared to 15 g.kg-1 . Forage mass and leaf proportion had no effect of NC and CP. Average daily gain, carcass gain, stocking rate and productivity were higher in animals fed NC ad libitum compared to those fed 15 g.kg-1 . The use of DDGS as a protein source showed no effect for the performance variables compared to soybean meal. Blood parameters of the cattle showed no effect of NC and FP. Diets with NC of 17 g kg-1 showed an increase of 8.93% in final gas volume (Vf). In diets with PF we observed Vf superior in 5.24% in relation to DDGS. xiii The digestibility of dry matter and organic matter after 48 h of incubation were higher by 7.95 and 9.13%, respectively in diets with NC of 17 g kg-1 . We conclude that there was no effect of NC and FP for the methane production variables. The use of DDGS as protein source in high concentrate diets (17 g.kg-1 of CP), is an alternative to replace soybean meal, increase individual performance and productivity per area in Nelore cattle in the pasture finishing phase, during the rainy season. The use of DDGS as a source of protein, at the level of 170 g kg-1 of inclusion, in high concentrate diets, presents lower in vitro digestibility of dry matter and organic matter, and lower volume of gases produced, without changes in methane production, compared to soybean meal. Diets with inclusion of 17 g kg-1 body weight of concentrate promote better in vitro digestion kinetic patterns.